Efektivitas Pemanfaatan Biogas Untuk Menunjang Ketahanan Energi (Studi Di Desa Pendoworejo Kecamatan Girimulyo Kabupaten Kulon Progo Daerah Istimewa Yogyakarta) - Dyah Sri Palupi (Universitas Gadjah Mada, 2015)
ABSTRACT The development of renewable energy was one of the crises of energy solutions. The purposes of the research were to analyzed the effectiveness of biogas utilization and examine the connection of that utilization with energy resilience at Pendoworejo. The research method was qualitative descriptive analysis approach. Total amount the biodigesters were 183 units. Purposive sampling technique was used to determined the samples. The total informants were 55 people. Data collection techniques included literature studies, observation, interviews, and documents studies. The research results were 30.26% able to used and 69.77% unable to used. The continuity of effectiveness in utilizations was for daily using in the category low (25.58%), sometimes in using in the category very low (4.65%) and damage in the category enough (69.77%). The biogas utilization or function effectiveness were for cooking in the category high (86.82%), for the generator set (3.1%) and others (10.08%) in the category very low. The effectiveness for providing the needs were providing all needs in the category very low (9.3%), part of the needs in the category low (20.93%) and not at all in the category enough (69.77%). The effectiveness of biogas utilization at Pendoworejo village for energy resilience were at low level. The expectation in the next the Pendoworejo village would be self-supporting in energy, but the energy resources of biogas at the village had not reached more than 60% of total required energy. The effectiveness of biogas utilization at Pendoworejo village currently were not being able to supported the energy resilience yetABSTRAKPengembangan energi terbaharukan merupakan salah satu solusi krisis energi. Penelitian bertujuan untuk menganalisis tingkat efektivitas pemanfaatan biogas dan mengkaji hubungan efektivitas pemanfaatan biogas di Desa Pendoworejo dengan ketahanan energi. Metode penelitian yaitu kualitatif dengan pendekatan analisis deskriptif. Jumlah biodigester 183 unit. Penentuan sampel dengan teknik purposive sampling. Jumlah informan 55 orang. Teknik pengumpulan data meliputi studi kepustakaan, observasi, wawancara, dan studi dokumentasi. Hasil penelitian yaitu 30,26% biodigester berfungsi dan 69,77% dalam kondisi rusak. Efektivitas kontinuitas pemanfaatan dan ketersediaan biogas yakni pemanfaatan harian dalam kategori rendah (25,58%), pemanfaatan kadang-kadang dalam kategori sangat rendah (4,65%) dan kondisi rusak dalam kategori cukup (69,77%). Efektivitas pemanfaatan atau fungsi yakni untuk memasak dalam kategori tinggi (86,82%), genset (3,1%) dan lainnya (10,08%) dalam kategori sangat rendah. dalam kategori sangat rendah (9,3%), sebagian memenuhi kebutuhan dalam kategori rendah (20,93%), dan tidak memenuhi kebutuhan dalam kategori cukup (69,77%). Efektivitas pemanfaatan biogas di Desa Pendoworejo termasuk rendah. Desa Pendoworejo diharapkan menjadi Desa Mandiri Energi, namun sumber energi dari biogas belum mencapai lebih dari 60%. Efektivitas pemanfaatan biogas di Desa Pendoworejo belum mampu menunjang ketahanan energi.